Diversity and Medical Care Implication of Scorpions in Hong Local Government Area, Adamawa State, Nigeria - Pakka, Fami E.; Wilson, Ataitiya; Mohammed, Chidama I.; Ahmadu, Dahiru (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
A research study on Diversity and Medical Care Implication of Scorpions in Hong Local Government Area, Adamawa State, Nigeria was carried out to determine the habitat characterization of scorpions,the diversity and abundance as well as the seasonal variation and distributions of scorpion in the area under study. Despite the notoriety of scorpions envenomation, worldwide distribution, medical, ecological and conservation importance, many families and genera of scorpions are yet to be studied. In this research, effort was intensified toward identifying species diversity in the study area. The local government was divided into two zones, the northern and the southern zone. Three localities were selected from the northern zone which were Garaha, Mijili and Kwarhi and three localities were selected from the southern zone which were Kram-Hong, Dzumah and Pella in which three study sites were chosen for the collection of scorpion; the Hills Farm Land and Residential Areas. A total of four hundred and five scorpions (405) scorpions were collected across the localities. Mijili gas thes highest abundance of scorpions with 48.15% of the specimen, while Kram-Hong shows the least abundance with 2.72%. in term of species abundance ,Hottentotta hottentotta was found to more abundant with 54.54% while the least was Pandinus imperator with 1.23%. with the respect to seasonal variation, results showed that scorpions are more available during raining season with 83.44% while dry season has the lowest abundance with 15.56%. with regard to monthly distribution, september has the highest distribution with 23.21% while January has the lowest distribution with 7.16%. The result of scorpions abundance based on the study sites shows that Hills has highest abundance with 46.17% compared with the collection of scorpions from the residential area with 23.70%. data on relative abundance of scorpions from micro habitat revealed that scorpions collected from bark of trees, under stones and pilled blocks shows highly significance difference with P <0.05 over that from garbage, crevice and gravels with lowest abundance of scorpions. In conclusion, the entire scorpions obtained were identified as indigenous species with the exception of Androctonus bicolor. Hottentotta hottentotta remains the widely distributed species found under stones, between bark of dry trees and between pilled blicks. Therefore, frequent identification and inventory of available species of scorpions and the study of this period of high occurrence would provide baseline data for risk reduction of scorpion envenomation and entomorphobia of dangerous and congeneric species.